Case report: a rare clinical presentation of a difficult diagnosis of dedifferentiated liposarcoma showing leiomyosarcoma phenotype in the ileocecal region - Kawasaki, Tomonori; Tashima, Tomoaki; Onohara, Kojiro; Hirano, Yasumitsu; Yamato, Misuzu; Shirotake, Suguru; Torigoe, Tomoaki; Yazawa, Yasuo; Hirasaki, Masataka; Wako, Masanori; Fujimaki, Taro; Ichikawa, Jiro (Frontiers in Oncology, 2024)
Dedifferentiated liposarcoma is a malignant lipomatous tumor that rarely occurs in the gastrointestinal tract, including the ileocecal region. In this case, computed tomography and magnetic resonance imaging showed no fatty mass located in the mesenteric or submucosal lesion, and positron emission tomography–computed tomography showed a high maximum standardized uptake value, collectively indicating the gastrointestinal stroma tumor and lymphoma. The pathological findings resemble leiomyosarcoma; the immunohistochemistry findings including mouse double minute 2 homolog and cyclin D-dependent kinase-4 and amplification of mouse double minute 2 homolog in fluorescence in situ hybridization just favored the diagnosis of dedifferentiated liposarcoma with leiomyosarcoma phenotype and not leiomyosarcoma. Recently, a new inhibitor for mouse double minute 2 homolog and cyclin D-dependent kinase-4 has been developed, and clinical trials for dedifferentiated liposarcoma are currently ongoing. This could change the treatment strategy drastically compared with other soft tissue sarcomas. Hence, a correct diagnosis of dedifferentiated liposarcoma is required.